Kajian Kuat Lentur Balok Beton Bertulang Komposit - Dika Ananditya; Adri Praditya; David Widianto; Hermawan . (G-SMART, 2019)
Demand for improvement of age concrete performance, durability and assessment of existing condition building with reinforced concrete structure have tendency to increase. The selection of appropriate methods taking into the economic aspects provides a rebuilt or retrofit option. Efforts that can be done in order to retrofit the beam structure, can be done in various ways, one of which is the use of chemical anchor. Repair using chemical anchor involves two elements, namely chemical HILTI HIT-RE 500 V3 and anchor. Both elements combine the existing beam with a new block to be a single composite beam. The use of HILTI HIT-RE 500 V3 can guarantee the monolithic nature of the structure components and transfer the voltage even though there is little cracking. The use of anchorage in concrete can increase the load that can be supported by 5.87% -8.91% and will increase with the length of the burial.This study aims to study the strength of reinforced concrete bone beam that is improved by chemical anchor method. The scope used is a beam-shaped specimen measuring 15 cm x 15 cm x 60 cm, monolith beam 15 cm x 30 cm x 60 cm, anchor steel bone diameter 13 mm, 24.9 MPa concrete (K-300) and chemical anchor HILTI HIT-RE 500 V3.The test results show that concrete composite increases the maximum acceptable load three times between 30 cm thick composite beam and 15 cm thick single beam. The maximum load of 30 cm thick monolith beam has increased by 1,5 times compared to 30 cm thick composite beam. The average maximum load that can be supported by a single 15 cm thick beam is 6.515 kg, 30 cm thick concrete monoliths 12.800 kg, and 30 cm thick concrete block is 19.267 kg.